Kānprapprung phūmithat phư̄a songsœ̄m khunkhā læ khwāmsamkhan dān mō̜radok thāng watthanatham Wat Phra Mahāthāt Wō̜ramahāwihān Čhangwat Nakhō̜n Sī Thammarāt sū kānsanœ̄ chư̄ pen lǣng mō̜radok lōk - Wirut Thinnakhō̜n (Mahāwitthayālai Walailak, 2018)
Conservation and revitalization of Wat Phramahathat Woramahawihan, Buddhist temple in Nakhon Si Thammarat Province, Southern Thailand.